2022
DOI: 10.1080/15592324.2022.2091305
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure change and transcriptome analysis of GA3 treatment on seed germination of moso bamboo(Phyllostachys edulis)

Abstract: Exploring the mechanism of Gibberellic acid (GA 3 ) treatment on seed germination of moso bamboo can lay a foundation for its future breeding and research. In this study, the germination-related indicators (germination rate, germination potential, vigor index, respiration rate) with different content of GA 3 treatment were measured, and the ultrastructure of moso bamboo seeds treated with low and high GA 3 concentrations was observed during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In our study, the starch content of the seeds treated with or without GA 3 significantly decreased with the germination process, and the starch content of the seeds treated with GA 3 was significantly lower than that of the seeds treated without GA 3 (Figure 6C) in the radicle emergence stage. Similar results were obtained by Li et al (2022), who found that GA 3 treatment accelerated the hydrolysis of starch in Phyllostachys edulis seeds. Consistent with the present results, the expression levels of two key starch-hydrolases, beta-amylase (SgBAM) and alpha-glucosidase (SgAGLU), were significantly up-regulated in the Bg group (Figure 6A).…”
Section: Role Of Carbohydrate-related Metabolism Pathways During Ga 3...supporting
confidence: 88%
See 1 more Smart Citation
“…In our study, the starch content of the seeds treated with or without GA 3 significantly decreased with the germination process, and the starch content of the seeds treated with GA 3 was significantly lower than that of the seeds treated without GA 3 (Figure 6C) in the radicle emergence stage. Similar results were obtained by Li et al (2022), who found that GA 3 treatment accelerated the hydrolysis of starch in Phyllostachys edulis seeds. Consistent with the present results, the expression levels of two key starch-hydrolases, beta-amylase (SgBAM) and alpha-glucosidase (SgAGLU), were significantly up-regulated in the Bg group (Figure 6A).…”
Section: Role Of Carbohydrate-related Metabolism Pathways During Ga 3...supporting
confidence: 88%
“…GAs also enhance the growth potential of the embryo by antagonizing ABA activity ( Finch-Savage and Leubner-Metzger, 2006 ). The molecular mechanisms of GA 3 -induced seed dormancy release have been explored using transcriptomic and/or metabolomic analysis in Fraxinus hupehensis ( Song et al., 2019 ), Leymus chinensis ( Li et al., 2021 ), Phyllostachys edulis ( Li et al., 2022 ), Panax notoginseng ( Ge et al., 2023 ), and Zea mays ( Han et al., 2023 ). However, the mechanism of seed dormancy release in different plants might be species-dependent ( Chibani et al., 2006 ; Lee et al., 2006 ; Pawłowski, 2007 ; Pawłowski, 2009 ; Deng et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Key metrics for assessing seed germination and vigor include germination rate, potential, index, and vigor index. 20 , 21 This study found that both acid and Al stress significantly impeded S. davidii seed germination. Under strong acid conditions (pH = 3.5), there was a marked decline in germination rate, index, and vigor compared to the control, indicating a suppression of germination ability and seedling vigor in a highly acidic environment.…”
Section: Discussionmentioning
confidence: 66%
“…Especially, the α-Xyl and β-D-Xyl weakened the endosperm cell wall by modulating the structure of xyloglucan during seed germination [28,29]. And the decomposition of starch could promote seed sprouting [30]. Thus, these proteins, which were related to metabolism, might paly crucial role in seed germination.…”
Section: Discussionmentioning
confidence: 99%